Adaptability and stability with multivariate definition of macroenvironments for wheat yield in Rio Grande do Sul - Szareski, Vinícius Jardel; Carvalho, Ivan Ricardo; Kehl, Kassiana; Levien, Alexandre Moscarelli; Rosa, Tiago Corazza da; Souza, Velci Queiróz de (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the adaptability, stability, and environmental stratification of wheat (Triticum aestivum) grown in 20 environments, in the state of Rio Grande do Sul, Brazil. The experiments were performed during four crop years, in five wheat growing regions, considering 20 distinct growing environments. In the presence of genotype x environment (GxE) interaction, the additive main effects and multiplicative interaction analysis (AMMI) method was used. This method combines variances of additive effects of genotypes and environments with the multiplicative effects of GxE interaction, and the obtained scores are displayed in biplot graphs, using the principal component analysis. The environments stratified by the factor analysis, and the macroenvironments were defined according to grain yield behavior. The patterns of adaptability and phenotypic stability for genotypes 'BRS 327', 'BRS 331', 'Fundacep Raízes', 'BRS 328', and 'BRS Guamirim' were obtained through the multivariate biometric approaches AMMI and the factor analysis. The definition of macroenvironments is intrinsic to peculiarities of the crop year in the state of Rio Grande do Sul, and there is similarity between the municipalities of Santo Augusto, Cachoeira do Sul, and São Luiz Gonzaga, as well as between Cachoeira do Sul and São Gabriel.
Keywords: Triticum aestivum; AMMI method; genotype x environment interaction; multiplicative model; principal component analysis